Representações sociais de gênero pela linguagem de moda em um grupo de estudantes do Ensino Fundamental II - Battisti, Francisleth Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research presents the Social Representations of Gender of secondary school students by the language of Fashion. This analysis indicates that the act of dressing produces representations that influence school social relationships between male and female students. This project focus on a qualitative character study, inside a State Secondary School in São Paulo State, for the purpose to identify the conceptions of students about sexuality and gender by the language of fashion. For this research we realize a focus group showing images and working with the technique of free associations intending to gather the perceptions, values, attitudes and ideas from the adolescents about the gender issues. We used the Social Representation of Gender Theory as an analytical category. We noticed that the conceptions brought by the adolescents still bring conservative, racist and homophobic discourses. We intend to contribute with the comprehension of the relationship sexuality / Fashion / school education, in addition to the interdisciplinary knowledge production

Esta pesquisa apresenta as Representações Sociais de Gênero de estudantes do Ensino Fundamental II pela linguagem de Moda. Essa análise entende que o ato de vestir produz representações que influenciam as relações sociais escolares entre alunos e alunas. Essa proposta centra-se em um estudo de cunho qualitativo, dentro de uma Escola Estadual de Ensino Fundamental II do interior paulista, com intuito de identificar as concepções das estudantes acerca da sexualidade e de gênero pela linguagem da moda. Para a realização desta pesquisa utilizamos um grupo focal apresentando imagens e trabalhando com a técnica de livre associação objetivando colher percepções, valores, atitudes e ideias das adolescentes a respeito das questões de gênero. Utilizamos a Teoria das Representações Sociais e Gênero como categorias de análise. Notamos que as concepções trazidas pelas estudantes ainda carregam discursos conservadores, racistas e homofóbicos. Pretendemos contribuir com a compreensão da relação sexualidade/moda/educação escolar, além da produção de conhecimento interdisciplinar
Keywords: Educação; Educação sexual; Moda; Representações sociais; Racismo; Homofobia; Conservantismo; Education